If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + 9) = 114 Reorder the terms: (9 + 7x) = 114 Remove parenthesis around (9 + 7x) 9 + 7x = 114 Solving 9 + 7x = 114 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 7x = 114 + -9 Combine like terms: 9 + -9 = 0 0 + 7x = 114 + -9 7x = 114 + -9 Combine like terms: 114 + -9 = 105 7x = 105 Divide each side by '7'. x = 15 Simplifying x = 15
| 2x+9=71 | | x^3+4x^2+4x-6=0 | | 4ab/4ab | | 3(x+12)=2x+51 | | 2(x+3)-6=5x+12 | | 14-5x=-7x+14 | | 3.61n=8+2.476n | | -10y=-130 | | 14=-15a+4a | | 7x-3x+9=12+x | | x^2+4s=27 | | 15=7+2u | | 5(x+2)-3=2 | | 6-9*0=-21 | | 5(3x-1)=4(3x-2) | | 6-9*3=-21 | | -6-9*9=-21 | | 6-9*-5=-21 | | 5(x+4)-x=16 | | -91=-7(6+5) | | 3x-19=30 | | -91=-7(8+5) | | 5x-1+3x=11+4x | | -91=-7(-7+5) | | (2x-5)(2x-5)=(x-1)(x-1) | | -91=-71(-5+5) | | 200=49-u | | 88=8 | | -2.8x=-5.6 | | 8*9+7=39 | | 8*-2+7=39 | | 8*3+7=39 |